(untitled) (The Pakistan Development Review, 1991)
The purpose of the present paper has been to quantify and discuss the implications of implicit taxes in Pakistan’s agriculture. The methodology of the paper consisted of derming the impon and expon parity prices of major agricultural commodities grown in Pakistan, by comparing them with domestic procurement prices. Although the analysis covered only four commodities, implicit tax rates in some of the years from 1970-71 to 1989-90 were as high as 75 percent for cenain commodities. It was only in the case of IRRI rice and sugarcane that domestic prices were above the world levels in some years of the period under consideration. When shown as a percentage of the value-added by agriculture, the taxes on these four commodities, net of the total budgetary subsidies on agricultural inputs, varied from 1.9 percent to 14.9 percent. These tax rates in agriculture compared favourably with the overall tax rates in Pakistan’s economy for most of the years. Judged in the light of the relative taxable capacities of agriculture and Pakistan’s economy as a whole, implicit taxes were much higher in agriculture than in the other sectors of the economy.